2021
DOI: 10.1088/1555-6611/abd3f8
|View full text |Cite
|
Sign up to set email alerts
|

Single-longitudinal-mode operation of a 2.09 μm holmium laser with anti-misalignment corner cube ring cavity

Abstract: A single-longitudinal-mode (SLM) 2.09 µm Ho:YAG laser with anti-misalignment corner cube ring cavity was demonstrated. Unidirectional components composed of a faraday rotator and half-wave plate were used to organize the travelling wave beam propagation and to eliminate the spatial hole-burning effect. The maximum SLM power was 728 mW. The corresponding slope efficiency achieved 23.42% and the optical conversion efficiency was 7.16%. Widely tunable wavelength outputs from 2090.43 nm to 2098.37 nm have been ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The output power decreased by 30% when the angle of the CCR was shifted by 11.8 • , proving the anti-misalignment of the ring oscillator with CCRs. Wu et al demonstrated a narrow linewidth laser with two CCRs at 2.09 µm with a power of 728 mW, the corresponding slope efficiency was 23.42% [21]. In injection-locked lasers, Zhang et al reported a 1.6 µm injection-locked laser system at a repetition rate of 143 Hz [22], which employed a ring oscillator with double CCRs as the slave laser, delivering the energy of approximately 2 mJ.…”
Section: Introductionmentioning
confidence: 99%
“…The output power decreased by 30% when the angle of the CCR was shifted by 11.8 • , proving the anti-misalignment of the ring oscillator with CCRs. Wu et al demonstrated a narrow linewidth laser with two CCRs at 2.09 µm with a power of 728 mW, the corresponding slope efficiency was 23.42% [21]. In injection-locked lasers, Zhang et al reported a 1.6 µm injection-locked laser system at a repetition rate of 143 Hz [22], which employed a ring oscillator with double CCRs as the slave laser, delivering the energy of approximately 2 mJ.…”
Section: Introductionmentioning
confidence: 99%